Simulation of production and water use efficiency of spring canola cultivars in warm and temperate climates - Sajjad Rahimi-Moghaddam; Khosro Azizi; Hamed Eyni-Nargeseh; Seyed Ahmad Kalantar Ahmadi (علوم محیطی)
Introduction: Canola is one of the most important oilseed crops all over the world. This oilseed crop is mainly utilized for its high oil content (with about 40–45% oil). However, in recent years, the area under cultivation of canola has decreased due to water scarcity. Applying drought-tolerant cultivars with high water use efficiency can help to develop the area under cultivation of canola and increase canola production. Therefore, the current study was conducted to assess the water use efficiency of spring canola cultivars in warm and temperate climates.Material and methods: This study investigated different cultivars as a strategy for increasing canola production and improving its water use efficiency under different climate types in Khuzestan and Lorestan provinces. For this purpose, four locations including Khoramabad and Kuhdasht in Lorestan Province as semi-arid climate regions and Dezful, and Shushtar in Khuzestan Province as hot and arid climate regions were selected. Daily long-term climatic data (including minimum and maximum temperatures, rainfall, and global radiation) were collected for these locations from Iran Meteorological Organization. In this study, Hyola308 (early-maturity), Hyola401 (mid-maturity), and RGS003 (late-maturity) cultivars were used. In order to simulate the growth and yield of canola in different locations, the APSIM-Canola model was employed. OriginPro 9.1 software was used for all statistical analyses and the generation of figures.Results and discussion: The results showed that grain yield, biomass, water use efficiency, grain weight, actual evapotranspiration, the average temperature during the canola growth period, and the length of the canola growth period were substantially affected by cultivar and region (climate type). According to the results, the highest grain yield and water use efficiency (3037 kg ha-1 and 6.9 kg mm-1 ha-1, respectively) were achieved for the mid-maturity cultivar (Hyola401). Furthermore, simulation results revealed that temperate and semi-arid regions compared to hot and arid regions increased grain yield, biomass and water use efficiency by 2507 kg ha-1, 10100 kg ha-1, and 2.7 kg mm-1 ha-1, respectively. Khorramabad × Hyola401 treatment had the highest water use efficiency, grain yield, and biomass (9 kg mm-1 ha-1, 4954, and 17943 kg ha-1, respectively) due to lower the average temperature during the canola growth period (10.9 ° C) and higher the length of the canola growth period (2424.9 day), while the lowest amount of these traits was recorded in Dezful × Hyola308 treatment (5 kg mm-1 ha-1, 1369, and 5514 kg ha-1, respectively).Conclusion: The results indicated that expanding canola cultivation in temperate regions can be used to boost canola production in Iran and to improve the sustainability of canola cultivation agroecosystems. Also, using a mid-maturity cultivar such as Hyola401 in both temperate and hot climate conditions can increase water use efficiency and sustainability of canola production agroecosystems through higher production per water consumption.